Teaching mathematics with the active thinking model and its impact on metacognitive thinking among the fourth literary students - Assist Prof. Dr. Haider Abdul Kareem Mohsen Al-Zuhairy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the research is to identify (Teaching Mathematics with the Active Thinking Model and its Impact on the Metacognitive Thinking of the Literary Fourth Students); The research sample consisted of (60) students of the fourth literary students, distributed equally into two experimental and control groups of (30) students in each group. , and check its psychometric properties; The researcher applied the test to the two research groups after the end of the experiment, and the results showed: The students of the experimental group who studied with the active thinking model outperformed the students of the control group who studied in the usual way in the metacognitive thinking test.